The genus Pachyseius Berlese, 1910 in Iran (Acari: Pachylaelapidae) - Babaeian, Esmaeil; Mašán, Peter; Saboori, Alireza (Zootaxa, 2016)
A new pachylaelapid mite Pachyseius persicus Babaeian & Mašán sp. nov. is described and illustrated, based on adult females collected from litter and soil detritus of forest habitat in Northern Iran (Mazandaran Province). The new species can be easily distinguished from the other congeners by the following female character states: (1) presternal shields absent; (2) sternal shield coarsely punctate-reticulate over entire surface; (3) ventrianal shield with four pairs of pre-anal setae; (4) post-stigmatic section of peritrematal shields terminally rounded, reaching slightly beyond the coxae IV; (5) exopodal shields II–III free, exopodal shields III–IV fused to posterior section of peritrematal shields; (6) idiosoma with 11 pairs of setae in soft integument; (7) trochanter I with five setae, tarsus II with three spur-like setae, tarsus IV with 17 setae. Two species of Pachyseius previously reported from Iran, namely Pachyseius angustus Hyatt, 1956 and Pachyseius humeralis Berlese, 1910, are reviewed and discussed, respectively, and both records are considered to be based on misidentifications.